MANAJEMEN MUTU PRODUK HORTIKULTURA DI HYPERMART PEKANBARU - Tengku Harunur Rasyid; Yeni Kusumawaty (Indonesian Journal of Agricultural Economics, 2018)
The presence of today's modern market has offer a complete shopping place known as the concept of "one stop shopping". Hypermart Pekanbaru has a vision and mission that emphasizes quality, including the quality of perishable fruit and vegetables. This study aimed to examine: (1) Diversity of agricultural products, especially horticulture available in Hypermart Pekanbaru; (2) Horticultural product quality standard applied by the company and (3) Fruit and vegetable quality control process implemented in Hypermart Pekanbaru. The research method used was case study, to understand in depth complex problems in Hypermart Pekanbaru. Primary data collection is done by observation and interview with management and company employees, while secondary data through literature study. The results showed that: (1) The diversity of horticultural products in Hypermart Pekanbaru consists of local fruit, imported fruit, local vegetables and imported vegetables; (2) The quality standard set by Department Produce Hypermart Pekanbaru is from the aspect of product freshness, product appearance, and product quality based on the shape, size, weight, texture and product packaging according to the characteristics of each fruit and vegetables and (3) Stages of quality control process fruits and vegetables that are implemented in Hypermart Pekanbaru include local supplier selection process, standardization of fruit and vegetable products according to predetermined criteria, and carrying out daily management activities especially maintaining hygiene aspects of storage area, preparation and sales of fruit and vegetables.